2022
DOI: 10.1111/hex.13470
|View full text |Cite
|
Sign up to set email alerts
|

Mapping definitions of co‐production and co‐design in health and social care: A systematic scoping review providing lessons for the future

Abstract: Objectives: This study aimed to explore how the concepts of co-production and codesign have been defined and applied in the context of health and social care and to identify the temporal adoption of the terms.Methods: A systematic scoping review of CINAHL with Full Text, Cochrane Central Register of Controlled Trials, MEDLINE, PsycINFO, PubMed and Scopus was conducted to identify studies exploring co-production or co-design in health and social care. Data regarding date and conceptual definitions were extracte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
91
0
10

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(124 citation statements)
references
References 60 publications
2
91
0
10
Order By: Relevance
“…In line with other reviews exploring co-production in health and social care research [5,53], we identified growth in publications using co-production in care home settings over the last decade. Whereas co-production research conducted in the health field began to appear as early as the 1990s, [5] the earliest study identified in this review was published in 2013.…”
Section: Wider Contextmentioning
confidence: 53%
“…In line with other reviews exploring co-production in health and social care research [5,53], we identified growth in publications using co-production in care home settings over the last decade. Whereas co-production research conducted in the health field began to appear as early as the 1990s, [5] the earliest study identified in this review was published in 2013.…”
Section: Wider Contextmentioning
confidence: 53%
“…'Ideal co-design' includes an equal partnership at all research stages that embraces the principles of elevating lived experience, co-governance, equity-centric, diversity, inclusion and capability building. 10,12 Regardless of reporting, co-design was incorporated to varying degrees across all research stages and principles, with challenges presented by lack of consistent reporting of a co-design definition or approach, consumer involvement and adherence to principles. Indeed, fewer than half of the studies included for this scoping review defined codesign (or similar method used), and there was no unifying definition across any of the studies.…”
Section: Discussionmentioning
confidence: 99%
“…10 Generally, definitions refer to co-design as a participatory approach that engages all potential end users (e.g., service providers and service users) to design something of 'value' (context dependent), 11 whereas others include the quality of these relationships through principles such as equity, power and trust. 10 Following recent work by two authors (consumer, A. C., and researcher, A. Y.)…”
Section: Introductionmentioning
confidence: 99%
“…The team, therefore, co-created and colearned. However, in terms of efficiency, it could have helped to first set shared values for the project, as Masterson (2022) noticed that shared values are fundamental for co-creating. Still, all members expressed their joy during the process.…”
Section: Discussionmentioning
confidence: 99%